Geometrical study of channel profile under incremental forming process: numerical simulation / Felix Dionisius...[et al.] - Dionisius, Felix; Sugiri, Sugiri; Endramawan, Tito; Haris4, Emin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Incremental forming is one of the innovative manufacturing technologies in plate sheet forming techniques. With the incremental forming process, plate formation can be as desired and also easily applied to the manufacturing with a limited number of products. This paper is conducted to find out the smallest geometry of deviation between the design with the results of the process and the best step-down selection using a single point incremental forming (SPIF). The variable variations used in this research was 2-6 (mm) of step-down where this process uses a punch tool in the form of a hemispherical / half ball and with 2 clamps. Numerical simulation method with explicit finite element model was used as a virtual experiment with the helical shaped tool movement. The tool moves to form a blank with a size of 12x160x200 mm into a channel profile with a speed of 8 mm/s. The result showed that the deviation between the product and the design has increased from step down 2-6 mm. The smallest deviations were 3.63 mm for x axis and 12,549 mm of total depth or 4.57% for y axis with 2 mm step down parameter. Whereas for step down 4 mm had the deviation of 3.9 mm and 13.853 of total depth. But for step down 6 mm had failed / damaged.